Deep level defects in 4H-SiC introduced by ion implantation: the role of single ion regime. (2nd November 2017) - Pastuović, Željko; Siegele, Rainer; Capan, Ivana; Brodar, Tomislav; Sato, Shin-ichiro; Ohshima, Takeshi
Abstract: We characterized intrinsic deep level defects created in ion collision cascades which were produced by patterned implantation of single accelerated 2.0 MeV He and 600 keV H ions into n -type 4H-SiC epitaxial layers using a fast-scanning reduced-rate ion microbeam. The initial deep level transient spectroscopy measurement performed on as-grown material in the temperature range 150–700 K revealed the presence of only two electron traps, Z 1/2 (0.64 eV) and EH6/7 (1.84 eV) assigned to the two different charge state transitions of the isolated carbon vacancy, V C (=/0) and (0/+). C – V measurements of as-implanted samples revealed the increasing free carrier removal with larger ion fluence values, in particular at depth corresponding to a vicinity of the end of an ion range. The first DLTS measurement of as-implanted samples revealed formation of additional deep level defects labelled as ET1 (0.35 eV), ET2 (0.65 eV) and EH3 (1.06 eV) which were clearly distinguished from the presence of isolated carbon vacancies ( Z 1/2 and EH6/7 defects) in increased concentrations after implantations either by He or H ions. Repeated C – V measurements showed that a partial net free-carrier recovery occurred in as-implanted samples upon the low-temperature annealing following the first DLTS measurement. The second DLTS measurement revealed the almost complete removal of ET2 defect and the partial removal of EH3 defect, while the concentrations of Z 1/2 and EH6/7 defects increased, due to the low temperature annealing up to 700 K accomplished during the first temperature scan. We concluded that the ET2 and EH3 defects: (i) act as majority carrier removal traps, (ii) exhibit a low thermal stability and (iii) can be related to the simple point-like defects introduced by light ion implantation, namely interstitials and/or complex of interstitials and vacancies in both carbon and silicon sub-lattices.